ATRT-07. Low-grade diffusely infiltrative tumor, SMARCB1-mutant: a clinical and histopathological distinct entity showing epigenetic similarity with ATRT-MYC. (3rd June 2022) - Thomas, Christian; Federico, Aniello; Bens, Susanne; Hellström, Mats; Casar-Borota, Olivera; Kordes, Uwe; Neumann, Julia E; Dottermusch, Matthias; Rodriguez, Fausto E; Lo, Andrea C; Cheng, Sylvia; Hendson, Glenda; et al.
Abstract: Most atypical teratoid/rhabdoid tumors (ATRTs) occur in infants, but children and adolescents may also be affected. ATRTs occurring in older patients often comprise the molecular subgroup ATRT-MYC. Recently, central nervous system low-grade diffusely infiltrative tumor with INI1 deficiency (CNS LGDIT-INI1) has been described as a rare low-grade lesion (Nobusawa et al. Am J Surg Pathol 2020;44:1459-1468). Little is known on the molecular relationship of CNS LGDIT-INI1 and ATRT. We therefore further explored a series of six CNS LGDIT-INI1. The median age of the four males and two females was 16 years (range: 10-28 years). All tumors were of supratentorial location and showed low to moderate cellularity, diffuse growth of inconspicuous small SMARCB1-deficient tumor cells and reactive pleomorphic neuronal and glial cells with retained SMARCB1-staining in the background. In addition, two cases also displayed a high-grade rhabdoid component. After DNA isolation, purification and bisulfite conversion, samples were subjected to DNA methylation profiling (MethylationEPIC BeadChip array). Using DNA methylation-based classification and the Heidelberg Brain Tumor Classifier (version v11b4), all tumors were classified as ATRT-MYC (median calibrated score: 0.97). On t-SNE analysis, DNA methylation profiles grouped closely together in proximity to ATRT-MYC. Follow-up information was available for four cases (including the two cases with a high-grade component). Patients received heterogeneous treatments (including chemotherapy according to AT/RT protocols) and experienced stable disease or complete remission after an observation time of three to 56 months. In conclusion, CNS LGDIT-INI1 is a clinically and histologically distinct entity with relatively favorable outcome. Nevertheless, epigenetic similarity with ATRT-MYC and the potential of malignant progression warrants close follow-up examinations. In line with recent developments of WHO nomenclature, we propose to refer to these tumors as "low-grade diffusely infiltrative tumor, SMARCB1-mutant".